2016
DOI: 10.1080/14740338.2016.1229301
|View full text |Cite
|
Sign up to set email alerts
|

Second generation antipsychotics in ‘real-life’ paediatric patients. Adverse drug reactions and clinical outcomes of drug switch

Abstract: SGAs safety data were consistent with the ones already known; however, there is still a need to improve the knowledge in pharmacovigilance field among clinicians. Switching to aripiprazole may be a valid alternative to risperidone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 44 publications
2
10
1
Order By: Relevance
“…This study aims to provide a comprehensive overview of all ICSRs spontaneously reported to EV (one of the largest pharmacovigilance databases) in the pediatric population with a huge variety of psychiatric disorders treated with risperidone and aripiprazole, contributing to define their safety profiles in real-world settings. In line with recent pharmacoepidemiological studies evaluating the safety profile of SGAs in the young population, we found that the largest proportion of ICSRs was reported for boys, and the most frequently reported suspected antipsychotic drug was risperidone (19,20). These findings are consistent with previous evidence showing that male adolescents are more likely than females to be prescribed atypical antipsychotics and that risperidone is the SGA most commonly prescribed to the young population due to a wider spectrum of indicated uses (21).…”
Section: Discussionsupporting
confidence: 91%
“…This study aims to provide a comprehensive overview of all ICSRs spontaneously reported to EV (one of the largest pharmacovigilance databases) in the pediatric population with a huge variety of psychiatric disorders treated with risperidone and aripiprazole, contributing to define their safety profiles in real-world settings. In line with recent pharmacoepidemiological studies evaluating the safety profile of SGAs in the young population, we found that the largest proportion of ICSRs was reported for boys, and the most frequently reported suspected antipsychotic drug was risperidone (19,20). These findings are consistent with previous evidence showing that male adolescents are more likely than females to be prescribed atypical antipsychotics and that risperidone is the SGA most commonly prescribed to the young population due to a wider spectrum of indicated uses (21).…”
Section: Discussionsupporting
confidence: 91%
“…Indeed, to date, the safety of these medications for long-term treatments in pediatric patients remains a subject of debate, and several important safety concerns previously highlighted in literature are still not yet resolved (13,15,(21)(22)(23). Therefore, it is clear that close and long-term monitoring of pediatric patients treated with APs in a real-world setting could be useful to clinicians in the process of tailoring the therapies for the single patient and for the identification and treatment of therapy-related conditions (e.g., metabolic dysregulation) as previously stated by other authors (24). In addition to that, such monitoring could be helpful for a better definition of the safety and tolerability profiles of these drugs especially in the long term, as highlighted by previous studies based in a realworld setting (25).…”
Section: Introductionmentioning
confidence: 94%
“…Moreover, in the last thirty years several targeted therapies were approved for the treatment of cancer and autoimmune diseases, but their long-term safety profile have not yet been completely defined. Since clinical evidence derived from pivotal studies could fail to address key safety questions, real world data (RWD; Ruggiero et al, 2012 ; Iolascon et al, 2013 ; Cammarota et al, 2014 ; Ferrajolo et al, 2014 ; Parretta et al, 2014 ; Woo, 2014 ; Menditto et al, 2015 ; Donati et al, 2016 ; Giardini et al, 2016 ; Rafaniello et al, 2016b ) should be considered complementary to those obtained from traditional RCTs.…”
Section: Introductionmentioning
confidence: 99%